Cross-Culture Adaptation and Psychometric Properties of the DrInC Questionnaire in Tanzanian Swahili - Zhao, Duan; Staton, Catherine A.; He, Qing; Mmbaga, Blandina Theophil; Vissoci, Joao Ricardo Nickenig (Frontiers in Public Health, 2018)
Aims: To develop Swahili versions of the Drinker Inventory of Consequences (DrInC) and evaluate its psychometric properties among a mixed population in Tanzania. Methods: A Swahili version of the DrInC was developed by a panel of bilingual Swahili and English speakers through translation and back-translation. The translated DrInC was administered to a sample of Tanzanian injury patients and a sample of the general population. The validity and reliability of the scale were tested using standard statistical methods. Results: The translated version of the DrInC questionnaire was found to have outstanding domain coherence and language clarity. The tested scale and subscales have adequate reliability (>0.85). Confirmatory factor analysis confirmed the five-factor solution by yielding adequate results. DrInC score is statistically significantly correlated with alcohol consumption quantity and the AUDIT score, suggesting that DrInC is able to predict alcohol use as well. Conclusions: This study presents the first validation of the DrInC questionnaire with injury patients and a general population and the first adaptations of the DrInC questionnaire in the Tanzanian and Swahili setting. DrInC instrument was found to have satisfactory psychometric properties, resulting in a new medical and social research tool in this setting.